TELAAH PERTIMBANGAN HAKIM DALAM PUTUSAN BEBAS TERDAKWA TINDAK PIDANA PENIPUAN (STUDI PUTUSAN NOMOR 799/PID.B/2021/PN JAMBI) - Muhammad Dedy; Bambang Santoso (Verstek, 2021)
This article aims to examine and find out the suitability of the considerations of the judge who handed down an acquittal in a fraud crime case with article 183 in conjunction with article 191 paragraph (1) of the Criminal Procedure Code. This article uses normative or doctrinal legal methods that are prescriptive and applied. The approach used in this article is a case approach. The use of legal materials includes primary legal materials and secondary legal materials. The technique of collecting legal materials uses library research by collecting legal materials related to the problem to be studied. The law material analysis technique used is the syllogism method which uses a deductive mindset. Based on the results of the research and discussion, it shows that in Decision Number 799/Pid.B/2021/PN Jambi, the considerations of judges who handed down acquittals in cases of fraud were in accordance with Article 183 in conjunction with Article 191 paragraph (1) of the Criminal Procedure Code. This is because the Prosecutor's evidence is still very minimal through the evidence of witnesses and letters to find material truth in this case. In addition, based on the results of the examination at trial the Judge was of the opinion that the second and third elements of Article 378 of the Criminal Code in the Public Prosecutor's indictment were not legally fulfilled so that the Judge handed down an acquittal against the Defendant.Keyword: Judge's Consideration; Evidence; Acquittal Verdict; Fraud